2010
DOI: 10.1016/j.memsci.2009.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Partial hydrogenation of soybean oil using metal-decorated integral-asymmetric polymer membranes: Effects of morphology and membrane properties

Abstract: Three phase reaction schemes pose numerous challenges to reactor design due to the slow diffusional mass transfer of reactants from the gas phase through a liquid to the active sites of the catalyst. An example is partial hydrogenation of vegetable oil which is traditionally carried out in a batch autoclave by bubbling hydrogen gas though a slurry of oil and solid catalyst particles containing Ni. Unwanted trans fatty acids (TFA) are formed during this process due to the scarcity of hydrogen at the active cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The hand-cast membranes studied here have a range of hydrogen fluxes J H2 and selectivities α H2/N2 depending on the skin thickness and the presence/absence of skin defects that may allow some gas permeation by convection rather than diffusion through An earlier study in our lab evaluated platinum decorated polymeric membranes having a range of hydrogen fluxes, skin defects, and catalyst loadings 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hand-cast membranes studied here have a range of hydrogen fluxes J H2 and selectivities α H2/N2 depending on the skin thickness and the presence/absence of skin defects that may allow some gas permeation by convection rather than diffusion through An earlier study in our lab evaluated platinum decorated polymeric membranes having a range of hydrogen fluxes, skin defects, and catalyst loadings 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The metal was deposited as a network of large interconnected islands with some exposed polymer membrane area. One of our previous studies showed that the catalyst distribution as obtained gave high hydrogenation rates with minimum formation of TFA 14 .…”
mentioning
confidence: 87%
“…As novel applications for high performance polymers and membrane separation processes are developed, an understanding of the sorptive capacity and diffusion properties of the chemical species in which they are in contact must be further investigated. Examples of such novel applications include solvent resistant nanofiltration [1][2][3] and polymeric membrane reactors [4][5][6][7]. In these applications the polymeric membranes encounter chemical environments not often seen in more traditional gas separation processes, including exposure to highly plasticizing and swelling agents such as alcohols, furans, aromatics, and related hydrocarbons [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical crosslinking is often employed in membrane based gas separation applications where one or more of the gases cause significant plasticization, as in the removal of CO 2 from natural gas, and in the area of solvent‐resistant nanofiltration where the separation of harsh liquid organic solvents is often encountered . A growing application for membranes that also potentially encounters harsh gas and liquid chemical environments is the use of the membrane in a chemically reactive system, or membrane reactor . Membrane reactors offer a unique approach combining reaction and separation of desirable products or selective delivery of reactants into catalytic systems at controlled rates and location.…”
Section: Introductionmentioning
confidence: 99%
“…This study is motivated by our continued work on applying asymmetric polyimide membranes for membrane reactor applications in three‐phase hydrogenation reactions . Matrimid was chosen for the membrane reactor application and this study, because it is a commercially available polyimide with a glass transition temperature of 320 °C and is known to be stable in a wide range of chemical environments .…”
Section: Introductionmentioning
confidence: 99%